Successful Outcomes for Whom and for What?; Comment on "Government Actions and Their Relation to Resilience in Healthcare During the COVID-19 Pandemic in New South Wales, Australia and Ontario, Canada" - Karina Aase (Kerman University of Medical Sciences, 2022)
The coronavirus disease 2019 (COVID-19) pandemic is the case of a complex global crisis that requires resilient performance across all levels of healthcare systems worldwide. The analysis of government actions during the COVID-19 pandemic in Australia and Canada by Smaggus et al raises the possibility for a much needed and essential debate on the notion of outcomes in the resilience in healthcare literature. Government actions have downstream effects on stakeholders' capacity for resilience throughout the healthcare system. Yet, outcomes are fluent, multifaceted and dependant on time, space, and stakeholder perspectives. It is appropriate and timely for the resilience in healthcare field to better grasp the nuances of successful outcomes in complex adaptive systems.